Speaker Independent Speech Based Telephony Service for Agro Service using Asterisk and Sphinx 3 - Deka, Aniruddha; Deka, Manoj Kumar (International Journal of Computer Sciences and Engineering, 2025)
In this paper we describe the design of telephony Automatic Speech Recognition (ASR) System which can be used by low literate users. For this purpose we have deploy a spoken query system over Asterisk server using Bluetooth enabled mobile as client interface . Bodo speech data are collected by using the developed IVR module form BTAD area. All incoming calls are handled by Asterisk Server i.e. Computer telephony interface (CTI). The system asks to prompt 31 different words in Bodo which include Bodo digit, agricultural word and Yes/No. The collected speech is manually transcript and labeled for ASR system training. We discuss our experiences and fieldwork which includes design of the IVR using asterisk, Bodo ASR engine using sphinx and related study in the field of agricultural domain. We also evaluate low cost, rapidly deployable speech technologies for new languages as a means to improve equitable, affordable access to information technology (IT). The performance of a speech recognizer built using Bodo language is evaluated on the basis of word error rate and we 77.24 % word accuracy in training mode and 72.12 % in testing mode.